The stepping threshold test for reactive balance: validation of two observer-based evaluation strategies to assess stepping behavior in fall-prone older adults - Adams, Michael; Brüll, Leon; Lohkamp, Monika; Schwenk, Michael (Frontiers in sports and active living, 2021)
Introduction: Measurement of reactive balance is critical for fall prevention but is severely underrepresented in the clinical setting due to the lack of valid assessments. The Stepping Threshold Test (STT) is a newly developed instrumented test for reactive balance on a movable platform, however, it has not yet been validated for fall-prone older adults. Furthermore, different schemes of observer-based evaluation seem possible. The aim of this study was to investigate validity with respect to fall risk, interpretability, and feasibility of the STT using two different evaluation strategies.Methods: This study involved 71 fall-prone older adults (aged ≥ 65) who underwent progressively increasing perturbations in four directions for the STT. Single and multiple-step thresholds for each perturbation direction were determined via two observer-based evaluation schemes, which are the 1) consideration of all steps (all-step-count evaluation, ACE) and 2) consideration of those steps that extend the base of support in the direction of perturbation (direction-sensitive evaluation, DSE). Established balance measures including global (Brief Balance Evaluations Systems Test, BriefBEST), proactive (Timed Up and Go, TUG), and static balance (8-level balance scale, 8LBS), as well as fear of falling (Short Falls Efficacy Scale—International, FES-I) and fall occurrence in the past year, served as reference measurements.Results: The sum scores of STT correlated moderately with the BriefBEST (ACE: r = 0.413; DSE: r = 0.388) and TUG (ACE: r = −0.379; DSE: r = −0.435) and low with the 8LBS (ACE: r = 0.173; DSE: r = 0.246) and Short FES-I (ACE: r = −0.108; DSE: r = −0.104). The sum scores did not distinguish between fallers and non-fallers. No floor/ceiling effects occurred for the STT sum score, but these effects occurred for specific STT thresholds for both ACE (mean floor effect = 13.04%, SD = 19.35%; mean ceiling effect = 4.29%, SD = 7.75%) and DSE (mean floor effect = 7.86%, SD = 15.23%; mean ceiling effect = 21.07%, SD = 26.08). No severe adverse events occurred.Discussion: Correlations between the STT and other balance tests were in the expected magnitude, indicating convergent validity. However, the STT could not distinguish between fallers and non-fallers, referring to a need for further studies and prospective surveys of falls to validate the STT. Current results did not allow a definitive judgment on the advantage of using ACE or DSE. Study results represented a step toward a reactive balance assessment application in a clinical setting.
Gesehen am 14.12.2021